Low Adherence to the Mediterranean Diet Is Associated with Poor Socioeconomic Status and Younger Age: A Cross-Sectional Analysis of the EpiDoC Cohort - Mendonça, N (2022)
The Mediterranean diet (MD) is recognized as one of the healthiest dietary patterns as it has been consistently associated with several beneficial health outcomes. Adherence to the MD pattern has been decreasing in southern European countries for the last decades, especially among low socioeconomic groups. The aim of this study was to assess the adherence to the MD in Portugal, to evaluate regional differences, and explore associated factors (sociodemographic, economic, and lifestyles behaviors). This study used the third data collection wave of the Epidemiology of Chronic Diseases Cohort Study (EpiDoC 3). MD adherence was assessed using the Portuguese-validated MD adherence score (MEDAS) questionnaire. Non-adjusted and adjusted logistic regression models were used to assess the risk factors for low MD adherence and individual MEDAS items. In this cross-sectional evaluation of the EpiDoC 3 cohort study (n = 5647), 28.8% of the Portuguese population had low adherence to a MD. Azores and Madeira had lower adherence to the MD than the rest of the country. Younger individuals in lower income categories (e.g., ORfinding it very difficult = 1.48; 95% CI 1.16-1.91) and with a lower educational level (e.g., OR0-4 years = 2.63; 95% CI 2.09-3.32) had higher odds of having a lower adherence to the MD. Portuguese adults have a high prevalence of low adherence to the MD, especially among those who are younger and have lower socioeconomic status. Public health policies to promote adherence to the MD should pay special attention to these groups.